Dr Alexander Majkowski: A physician and Kashubian writer and poet - Anna Kotulska; Eugene J. Kucharz (Acta Medico-Historica Rigensia)
Kashubians known also as Kassubians (in Kashubian language: Kaszëbi) are the Slavonic ethnic group inhabiting the Eastern Pomerania in Poland. They speak the Kashubian language that is classified as the West Slavonic language belonging to the Lekhitic group of languages. Kashubians are the direct descendants of Pomeranians [1]. The Pomeranians came into the northern part of Poland about the 5th century AC. The region they lived is now known as Pomerania. The oldest mention of the region’s name is a seal of prince Barnin the First of Pomerania from the 13th century.